Varicella zoster virus anterior uveitis complicated by thalamic stroke - Casey L. Anthony; Anastasios P. Costarides; Steven Yeh; Jessica G. Shantha (Journal of Ophthalmic Inflammation and Infection, 2021)
Abstract We report a case of varicella zoster virus (VZV)-associated anterior uveitis in a patient with weight loss, arthritis and signs of inflammatory bowel disease. Her clinical course included the development of a thalamic stroke secondary to VZV cerebral vasculopathy. Following antiviral therapy, the patient’s neurologic symptoms recovered and her ophthalmic findings improved.